Innovativeness as an Enssential Part of Entrepreneurial Training in Developing the Competitive Advantage: Terengganu Creative Industry (Global Journal of Human-Social Science, 2011)
Basically the main objective of this study is to measure the significance of entrepreneurial training of innovativeness toward the competitive advantage in Terengganu creative industry This paper will look into the influence of innovativeness in four major business elements there are product innovation production innovation generating source of supply and management structure Furthermore the moderating effect of utilising market opportunity was also investigated This study was conducted by distributing questionnaires to 107 creative entrepreneurs who are registered in Kraftangan Malaysia Terengganu However they are only 105 respondents returned the questionnaires Analysis of the data revealed that the entrepreneurial training of innovation with the four major business elements e g product development production source of supply and management structures are weakly correlate with competitive advantages In addition the moderating of utilising market opportunities make the relationship of entrepreneurship training of innovations and competitive advantage become very weak correlation These findings indicated that most of creative entrepreneurs are not excited to practice the innovation in their business In fact most of them are not desire to utilised the market opportunities as a supportive to their entrepreneurship training of innovations toward the competitive advantage
Keywords: Innovation; competitive advantage; entrepreneurship training; entrepreneurship education; creative industry; Malaysia